Bounding societi(es) : Belonging and categories of identification in Israel/Palestine - Carter Hallward, Maia (Hagar: Studies in Society and Culture, 2007)
Although the Israeli-Palestinian conflict is often portrayed in essentialist terms using identity markers based on religion, language or ethnicity, most Israelis and Palestinians have murkier boundaries when pushed to define who is included in their community of belonging. This article explores the negotiation of identity categories among Palestinians and Israelis who engage in cross-border work, despite the dominant discourse of separation and difference, as a means of exploring how more inclusive boundaries of belonging might be encouraged in areas of ethno-national conflict and social exclusion. Because those Israeli citizens with Palestinian heritage (often called Arab Israelis) defy easy naming regimes, the article focuses primarily on activists in Ta ’ayush, the Arab-Jewish Partnership, as a means of exploring how categories of identity emerge out of the process of creating and maintaining such a partnership. Using a boundary-focused approach, the article traces ways in which activists define categories of "self” and "other” through action, engagement and shared ideals.